Description of -mA/-mAK Structures in Turkish from Perspective of Second/Foreign Language Pedagogy - (:unkn) unknown (TURKISH EDUCATION ASSOC, 2019)
Views on language education have changed along with developments in global society. Today, most learners seek to acquire a foreign language for daily communication. Consequently, instructors focus on communicative activities in language classrooms. When performing such activities, the most challenging issue for teachers is to create accurate and consistent grammatical content in harmony with communicative activities. In language education literature, triad classifications are often used to classify grammatical content: form, function and use. In this study, I introduce the grammatical content classifications mentioned in the literature and then classify -mA and -mAK suffixes, one of the most difficult subjects for learners of Turkish. With this aim, I review both reference grammar and textbooks, the kind of resources typically used by classroom teachers, who do not have time to perform an in depth linguistic description. With this in mind, the study focuses on the classification of the information depicted by linguistic resources. As a result, the form, function and usage characteristics of the -mA and -mAK suffixes are listed item by item and sample lesson content is presented. This research will help instructors of Turkish to construct the content of their lessons and gain a new perspective on grammar teaching.
Keywords: Second language; Foreign language; Pedagogy; Turkish; Grammar; Document analysis